Adopsi Teknologi Budidaya Kelapa pada Populasi Terserang Hama Sexava di Kabupaten Kepulauan Talaud - TORAR, DANIEL J. (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
Adoption of Coconut Cultivation Technology on Attacked SexavaPopulation in Talaud Island RegencyThis research was conducted by survey method with descriptive-correlational approach. The research was conducted in Kabaruan and Beo Sub District in Talaud Island Regency. Total of two villages were chosen randomly in each Sub District. In each village, 30 farmers were chosen randomly as respondents, making total of 120 farmers.The result showed that the adoption level of technology of coconut cultivated in Talaud Island Regency could be divided in to three categories, low level (35.83%), moderate (50.83%), and high level of adoption (13.33%).